Luz no Candeeiro : vínculos de pertencimento em torno do memorial de uma chacina no Centro Histórico de Cuiabá - Silgueiro, Gabriela Rangel (2019)
This dissertation presents the materialization of the Memorial to the Luminaire Alley Slaughter and some attributions of meaning to it. The triple murder killed three underaged, 13 to 16-year-old, in Cuiabá in 1998. Ethnography allowed the identification of how people who live in street situation appropriated the cultural asset, in the condition of survivors, while holding a collective memory built by children who were victims of violence and are linked to the Memorial by this factor. Historical documents (newspapers and digital media) together with the ethnography allowed the identification of the context of the Memorial installation and the forces related to its design and installation. The sculpture was made by a group of human rights activists who met in the 1980s and 1990s at the St. Benedict Church, a church erected by a black brotherhood. From this Memorial, I describe the bonds of belonging of the street population related to the narrative and places to which meanings have been attributed along the twenty years of the Memorial’s existence. The work also addresses the representations of the city administration and of the National Institute of Historical and Artistic Heritage (IPHAN) about the Memorial. The observation of the different representations allowed the identification of the contrasts between the meanings attributed to the Memorial by its holders, by the city administration and by IPHAN. The spaces to which the survivors attribute meanings are also contrasted with the meanings attributed by their neighbors. Finally, the historical presence of black people is presented as the background where meaning conflicts are currently unfolding.